KNOWLEDGE, SOURCES OF INFORMATION AND EXPERIENCES OF PUBERTY AMONG FEMALE ADOLESCENTS IN JUNIOR SECONDARY SCHOOLS IN IBADAN SOUTH-WEST LOCAL GOVERNMENT, NIGERIA (2014)
Puberty is a major biological change in adolescence that is characterised by physical, social and emotional development. In Nigeria, most female adolescents are not well informed about puberty before they experience it and more information is required on young adolescents' knowledge and experience of puberty. This study was designed to investigate the knowledge, information sources and experiences of puberty among junior secondary school female adolescents in Ibadan South-West Local Government Area (LGA), Oyo State, Nigeria. This cross-sectional survey used a five-stage sampling technique in selecting the LGA, wards, schools, arms of classes and 420 female adolescents between the ages of 10-14 years in junior secondary classes. Data were collected using a pre-tested Focus Group Discussion (FGD) guide and a semi-structured questionnaire. The questionnaire included a 16-point knowledge scale and questions on sources of information of puberty, experiences of puberty and menstruation. Knowledge scores of 0-7, >7<12 and ?12 were rated as poor, fair and good respectively. The six FGDs conducted were analysed using thematic approach and quantitative data were analysed using descriptive statistics, Chi-square test and logistic regression at 5% level of significance. Mean age was 13.0 ± 0.9 years. About 23% had good knowledge of puberty and it increased with respondents' class: J.S.S.1 (3.1%), J.S.S.2 (25.8%) and J.S.S.3 (71.1%). Those in J.S.S.2 (OR 0.1, 95% C.I:0.1-0.3) and J.S.S.1 (OR 0.3, 95% C.I:0.2-0.5) were less likely to have good knowledge of puberty compared with those in J.S.S.3. Majority (82.1%) had heard about puberty from school teachers (65.5%) being the major source of information. The preferred source of information of puberty was mothers (42.4%) and other sources were school teachers (40.5%), doctors (6.4%), sisters (5.0%), books/magazines (3.3%), films/videos (1.2%), friends (0.7%) and Internet (0.5%). All the respondents had experienced at least one of the changes that occur in puberty. Ninety nine percent had developed breasts out of which, 84.0% claimed they experienced pain when their breasts were developing. Sixty-seven percent had started menstruating with the age range at menarche being 8-14 years. Of this, 84.5% experienced menstrual problems. Headache and abdominal pain (47.9%) were the most reported menstrual problems experienced. About (61.5%) who experienced menstrual problems did not seek medical help and this was confirmed by FGD participants who attributed it to financial constraints and some felt that menstrual problems were normal. Methods employed by participants to address menstrual problems included: taking hot water or tea, herbs, salt and water, garri and salt and having some rest. Items and activities avoided during menstruation included sugary foods, physical exercise, going to school and engaging in sexual relationship. Young adolescents, especially those in junior secondary class one and junior secondary class two in Ibadan South-West Local Government Area did not have good knowledge of puberty with mothers being the most preferred source of education. Therefore, mothers, teachers and peer educators should be trained by the school and health authorities to better educate the girl child on puberty.